To the question on elaboration of evidence-based principles of prevention at the problem of suicide among young people. (Journal of Educational Sciences, 2016)
In article attempts of theoretical generalization of the problems of the prevention of suicide among young people. Also based on the study of fundamental positions in the fi eld of suicide prevention, scientifi cally grounded principles of prevention of the problem of suicide among young people. Particularly the prevention of suicidal problems in society, its principles, the basic aspects and types of existing socio-preventive measures. The authors on the basis of the analysis of the experience of foreign countries and CIS countries on the prevention of suicide and to introduce anti-suicide programs come to the conclusion that in many countries until recently responsible for the recognition of signs and symptoms of suicide was the exclusive prerogative of experts in the fi eld of mental health, and only in recent times, efforts were made to train other professionals to effectively respond to suicidal behavior (including specialists of primary medical aid, the hot line operators, teachers, etc).In the article generalizes the experience of foreign countries and CIS countries on the prevention of suicide, the authors come to the conclusion that gained abroad and in the post-Soviet space experience, can be used as positive examples for the development of anti-suicide programs.In outlining the specifi cs of the prevention of suicide among young people and analyzing the available suicidology and psychology principles suicide prevention, the authors offer and scientifi cally examine modernscientifi c principles of prevention of the problem of suicide among young people: the principle of reciprocity; consolidate efforts; the exclusion principle and the principle of vital activity consciousness.The principle of reciprocity, the authors justify the theoretical position, proving that any process is reversible, if not started yet. The principle of consolidation of efforts due to the fact that at the present stage much attention is paid to the activities of educational institutions in the sphere of health care (physical and psychological) of children and adolescents, however, necessary to consolidate the efforts of school (high school) and family. The principle of exclusion authors substantiated by the fact that the positive factors reject negative under certain conditions and conducting a purposeful pedagogical work). However, positive factors (also calledantisocially barrier) represents a sepa rate personal installation (experiences) that prevent the formation of suicidal behavior or implementation of suicidal acts. The principle of vital activity consciousness, according to the authors based on the mechanism of the vital activity of the individual. In the formulation of the principle of vital activity consciousness authors were based on the developed in the 30-ies S. Rubinstein main principle of the unity of consciousness and activity, according to which the psyche and consciousness forming in the activity, activity and manifested. In accordance with this provision, suicidal behavior is closely associated with the anti – or vital activity consciousness.Also, the design principle of vital activity consciousness, the authors relied on the natural-scientifi c theory of vital activity, which suggests that organic matter can only be created in plant or animal organisms, because they are subjected to the vitality (only under its infl uence can be formed complex organic substances). Therefore, the main aspect of vital activity consciousness, in their opinion, is to strengthen the vitality of man.
Keywords: suicide prevention suicide prevention principle; positive thinking